A Reinforcement Sensitivity Theory of Violent Extremist Propaganda: The Motivational Pathways Underlying Movement Toward and Away From Violent Extremist Action - Shortland, Neil; Portnoy, Jill; McGarry, Presley; Perliger, Arie; Gordon, Thomas; Anastasio, Natalie (Frontiers in Psychology, 2022)
Anecdotal evidence supports than engaging with violent extremist content online facilitates the radicalization process. However, there is a consistent lack of empirically grounded research to provide insight into the psychological process through which this influence occurs (if at all). As such, most theories often fail to accommodate both the multifinality (the concept that many people are exposed to violent extremist material, yet never engage in violent extremism), and equifinality (the concept that people can view a range violent extremist content, yet all end up engaging in violent extremism) that naturally is observed in those who engage with violent extremist content online and those who engage in violent extremist behavior. This paper presents Reinforcement Sensitivity Theory (RST) as a theoretical framework to inform understanding of the process that governs the interaction between violent extremist material online and engaging with violent extremism. RST is a motivational theory which has been applied to a range of benevolent and deviant behaviors. Specifically, we argue that RST is suitable to explain the effect of violent extremist content online because (1) it outlines multiple differentiated motivational pathways that can account for mutlifinality and equifinality observed in those who engage in violent extremist behavior and (2) the extant neurological and psychophysiological research using RST provides a empirically-supported framework for developing both research methods and verifiable hypotheses to advance our understanding of how, if at all, violent extremist content online contributes to the process of radicalization.